A one-pot two-enzyme system on the production of high value-added D-allulose from Jerusalem artichoke tubers. (January 2020) - Zhu, Ping; Zeng, Yan; Chen, Peng; Men, Yan; Yang, Jiangang; Yue, Xiaoping; Zhang, Jiangang; Zhu, Yueming; Sun, Yuanxia
Graphical abstract: Inulin in Jerusalem artichoke was hydrolyzed and completely converted into high-fructose syrup containing D-allulose by one-pot two-enzyme system. Highlights: High value-added D-allulose was produced using JA tubers through the one-pot two-enzyme system. Enzymes were extracellularly expressed to decrease cost and enhance thermal stability. Inulin in JA could be almost totally converted into monosaccharide with high efficiency. Abstract: A one-pot two-enzyme reaction system was developed to produce high-fructose syrup (HFS) containing healthy rare sugar d-allulose from Jerusalem artichoke (JA). Inulin in JA was converted through the cascade reaction of a novel exo-inulinase from Bacillus velezensis (BvInu) and D-allulose 3-epimerase from Ruminococcu s sp. (RDAE). BvInu and RDAE were expressed in Bacillus subtilis and successfully secreted into the supernatant, which decrease the production cost and avoid enzyme purification. The optimal temperature and stability of extracellular BvInu significantly increased, thereby promoting the catalytic activity of the two enzymes for the cascade reaction in one pot. Inulin in JA powder was almost completely converted into monosaccharides in the treatment with the optimal ratio of BvInu : RDAE (80 : 40 U/g inulin) at 50 °C for 2 h. The ratio of D-glucose, D-fructose, and D-allulose in the product was approximately 1:3:1, and the yield on JA powder was 67%. The system exhibits potential high-valued application of non-grain crops on producing HFS with D-allulose.